Application of Goal Programming Integrated Multi-Criteria Decision Making Approaches for the Stock Area Selection Problem of an Automotive Company - İlker Küçükoğlu; Betul Yagmahan; Ahmet Onaylı; Ezgi Didem Çayhan; Merve Ünal (International Journal of Supply Chain Management, 2017)
This study considers a stock area selection problem (SASP) of an automotive company which includes limited space. The SASP of the company consists of alternative locations which have different technical features and some specific criteria to select the locations. The aim of the problem is to find best stock areas from the alternatives that will be constructed. In order to solve the SASP of the company four different approaches are taken into account where each approach integrates a fuzzy multi-criteria decision making (MCDM) method within a preemptive goal programming (PGP) model. The main difference between the proposed approaches is the fuzzy MCDM methods used in the solution procedure where the considered methods are a fuzzy AHP (Analytic Hierarchy Process) method, a fuzzy TOPSIS (Technique for Order Preference by Similarity to Ideal Situation) method, a fuzzy PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluation) method, and a fuzzy VIKOR (VlseKriterijumska Optimizacija I Kompromisno Resenje in Serbian) method. Each solution approach consist of two stages where the alternatives are evaluated with respect to qualitative criteria by using fuzzy MCDM methods, and then PGP model is operated for quantitative criteria and the alternative scores obtained in the first stage. As a result of the computational application of the proposed solution methodology, the best alternatives are selected to construct in the company by comparing the results of four solution approaches.